An InSb-based magnetoresistive biosensor using Fe3O4 nanoparticles - Kim, Sung Jong; Lee, Seung-Woo; Song, Jin Dong; Kwon, Young-Wan; Lee, Kyung-Jin; Koo, Hyun Cheol (ELSEVIER SCIENCE SA, 2018)
A magnetoresistive biosensor was demonstrated using an InSb-based semiconductor channel. The Fe3O4 nanoparticle was linked with a target antigen via a capture antibody in the reagent, and a detection antibody immobilized on an InSb channel was shown to selectively bind to the antigen-capture antibody-nanoparticle complex. The detected magnetic nanoparticles produced a stray magnetic field that induced a change in the resistance of the channel due to the Lorentz force. The antigen concentration was proportional to the number of nanoparticles attached to the sensor surface, and hence could be determined by measuring the magnetoresistance level of the sensing channel. This antigen-antibody reaction sensor was shown to detect an extremely small amount of liver cancer antigen, at a concentration as low as 1 pg/ml. The systematic tests we carried out also confirmed the good selectivity and reusability of this biosensor. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: IRON-OXIDE NANOPARTICLES; SERUM ALPHA-FETOPROTEIN; SUPERPARAMAGNETIC NANOPARTICLES; HEPATOCELLULAR-CARCINOMA; IMMUNOASSAY; HEPATITIS; SENSORS; DESIGN; MRI